2018
DOI: 10.3390/f9060300
|View full text |Cite
|
Sign up to set email alerts
|

Workload, Exposure to Noise, and Risk of Musculoskeletal Disorders: A Case Study of Motor-Manual Tree Feeling and Processing in Poplar Clear Cuts

Abstract: Abstract:Motor-manual tree felling and processing (MMTFP) is among the most used options in timber harvesting operations and it is formally known to be a heavy job exposing the workers to safety hazards and harmful factors. Nevertheless, both workload and exposure depend on many operational, organizational, and worker-related parameters. Few studies have evaluated the ergonomics of such operations and fewer have been carried out using an integrated approach able to collect and interpret data for more than one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
50
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(63 citation statements)
references
References 39 publications
(41 reference statements)
2
50
2
Order By: Relevance
“…It is difficult to place the manual cultivation operations, in terms of difficulty and risks, amongst other forestry jobs, given the fact that heart response is dependent on many factors such as the age of subjects, gender and their operational environment. Nevertheless, in motor-manual felling, estimates from the same flat-land area and for a worker having an age close to the average of this study [17] were close to those found in this study. In steep terrain forests of Turkey, for instance, harvesting and forest nursery work was found to be difficult to moderate jobs with heart rate reserves of approximately 41 and 32%, respectively [39], while jobs such as cable work in steep terrain [40,41] and cable rigging [42] may take more effort.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…It is difficult to place the manual cultivation operations, in terms of difficulty and risks, amongst other forestry jobs, given the fact that heart response is dependent on many factors such as the age of subjects, gender and their operational environment. Nevertheless, in motor-manual felling, estimates from the same flat-land area and for a worker having an age close to the average of this study [17] were close to those found in this study. In steep terrain forests of Turkey, for instance, harvesting and forest nursery work was found to be difficult to moderate jobs with heart rate reserves of approximately 41 and 32%, respectively [39], while jobs such as cable work in steep terrain [40,41] and cable rigging [42] may take more effort.…”
Section: Discussionsupporting
confidence: 86%
“…Working predominantly with the back bent and twisted or bent forward and sideways (56.5% of the cases) may lead to health problems related to the lower back which is a known issue of forest operations jobs [14]. From this point of view, manual cultivation is a job that is even more hazardous compared to manual harvesting operations from Nordic countries [43] and close to that of motor-manual tree felling and processing operations from the area [17]. Compared to other kind of forestry-related partly mechanized jobs such as firewood processing [30] and wood debarking [44], manual cultivation seems to be riskier with the main problems coming from the back postures assumed during the work, since the arms and legs postures were found to be comfortable in most of the cases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Apart from causing occupational disorders (occupational deafness), it may also be the cause of accidents. In addition, noise causes mental function disorders -hinders thinking processes, weakens concentration, and finally favours imprecise performance of activities [6,7,8,9].…”
Section: Hazards In the Public Sector Of Forestrymentioning
confidence: 99%